2013
DOI: 10.4319/lo.2013.58.3.0803
|View full text |Cite
|
Sign up to set email alerts
|

Remote climate forcing of decadal‐scale regime shifts in Northwest Atlantic shelf ecosystems

Abstract: Decadal-scale regime shifts in Northwest Atlantic shelf ecosystems can be remotely forced by climateassociated atmosphere-ocean interactions in the North Atlantic and Arctic Ocean Basins. This remote climate forcing is mediated primarily by basin-and hemispheric-scale changes in ocean circulation. We review and synthesize results from process-oriented field studies and retrospective analyses of time-series data to document the linkages between climate, ocean circulation, and ecosystem dynamics. Bottom-up forci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
92
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 100 publications
(139 reference statements)
3
92
1
Order By: Relevance
“…In addition to the role of temperature, both atmospheric and oceanic circulations have been shown to play a key role in the long-term changes of marine populations [6,43,79,95], and may also influence the regime dynamics of the areas we studied. Our results support the hypothesis that climate dynamics may have a relevant role.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the role of temperature, both atmospheric and oceanic circulations have been shown to play a key role in the long-term changes of marine populations [6,43,79,95], and may also influence the regime dynamics of the areas we studied. Our results support the hypothesis that climate dynamics may have a relevant role.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon explains why all species in an ecosystem do not exhibit a shift [45,87], and, if a limited 2002 2003 1999 2000 2001 1989 1990 1991 1996 1997 1998 1992 1993 1994 1995 1984 1986 1985 1987 1988 1977 1978 1976 1979 1980 1981 1982 1983 1972 1973 1974 1971 1975 1960 1961 1962 1963 1968 1970 1969 1964 1965 1966 To address this question, we analysed the first three PCs originating from the PCAs performed for each ecosystem to reveal the NH biological state (BioPC), together with climate indicators (NHT, AO, PDO and AMO) and with long-term spatial variations in NHTs and SLPs. These variables were chosen because previous studies have suggested that temperature may affect the biogeographical distribution of many pelagic organisms [7,69], while changes in the main pressure centres can influence ocean circulation and the biological processes [41,43,[88][89][90], as well as local temperature [6]. We searched for potential lags in the responses of all regions to large-scale hydro-climatic forcing but no lag was observed using cross-correlation analysis and cross-correlograms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations